Water quality assessment in the Reventado's watershed, Cartago, Costa Rica, oriented to the development of indicators of sustainability - Villegas Osorio, Javier G. (1995)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 1995